Antioxidant properties of rambutan peel extract and sub-fractions and their potential as vegetable oil preservative - Sia, Winne Chiaw Mei (2015)
A number of tropical fruit peel has been known to possess high antioxidant activity,however, antioxidant data on the Malaysian tropical fruit peel is still lacking. In this study, red rambutan (Nephelium lappaceum) peel were reported to possess high antioxidant activities in comparison with peels obtained from tropical fruits, namely mangosteen (Garcinia mangostana), “langsat” (Lansium domesticum), Sapodilla (Manilkara zapota), passion fruit (Passiflora edulis), soursop (Annona muricata), and mango (Mangifera indica). The extraction method of rambutan peel was determined by using single factor experiments. Results showed that rambutan peel had the lowest EC50 (9.30±0.35 mg/g) and the highest TPC (359.60±20.85 GAE mg/g). Thus, rambutan peel was selected for further investigation on different extraction time (1 to 5 hours) and extraction temperature (25-60ºC). The extraction conditions of the red rambutan were determined to be 80% ethanol for 2 hours at 50ºC. The crude extract of the rambutan’s peel showed EC50 of 6.39±0.32 mg/g (DPPH), 333.70±13.35 mg/g (ABTS), 676.96±12.93 trolox equivalents mg/g (FRAP), 269.70±15.90 GAE mg/g (TPC) and 88.67±0.14% antioxidant activity (as measured by BCB). The crude extract of rambutan peel was then fractionated into three sub-fractions by using silica-packed column chromatography. Results reported the presence of phenolic compounds such as geraniin,ellagic acid and gallic acid. In the last part of this study, the crude extracts and the subfraction (SF II) reported with the highest antioxidant activity were supplemented into sunflower oil to study their effects in delaying lipid oxidation under accelerated conditions. Rambutan extract is a potential source of antioxidant. The oxidative activities of the crude extracts and sub-fraction (SF II) at all concentrations were significantly (p <0.05) higher than the control. Results reported that with two years storage period at ambient temperature, the sub-fraction, (SF II) at 300ppm, was observed to work more effectively than the synthetic antioxidant, t-tocopherol. SF II possessed a protective effect comparable with Butylated Hydroxyanisole (BHA). Therefore, rambutan extract could be used as a potential alternative source of antioxidant in the oil industry or other fat-based products to delay lipid oxidation.